1985
DOI: 10.1021/bi00327a037
|View full text |Cite
|
Sign up to set email alerts
|

Presence of oligomers at subcritical actin concentrations

Abstract: Measurement of the diffusion coefficient of G-actin using fluorescence photobleaching recovery reveals that a hydrodynamically larger species is formed in Mg2+-containing buffers but not in Ca2+-containing buffers. In buffer A (2 mM Tris-HCl, 0.2 mM CaCl2, 0.2 mM ATP, and 0.5 mM 2-mercaptoethanol, pH 8.0) and other Ca2+-containing buffers, the data indicate a single species with a diffusion coefficient of (7.98 ± 0.17) X 10™7 cm2/s. In Mg2+-containing buffers the average diffusion coefficient was (5.52 ± 0.06)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…(Here, monomeric actin is operationally defined as actin at concentrations less than the critical concentration. We recognize that dimeric and oligomeric actin may be present and contribute to the observed ATP hydrolysis (Newman et al, 1985).) This monomeric actin ATPase activity is markedly higher with Mg 2+ rather than Ca 2+ bound to the high affinity site .…”
Section: Influence Of the Bound Cation On Monomer Actin Atpase Activitymentioning
confidence: 85%
See 2 more Smart Citations
“…(Here, monomeric actin is operationally defined as actin at concentrations less than the critical concentration. We recognize that dimeric and oligomeric actin may be present and contribute to the observed ATP hydrolysis (Newman et al, 1985).) This monomeric actin ATPase activity is markedly higher with Mg 2+ rather than Ca 2+ bound to the high affinity site .…”
Section: Influence Of the Bound Cation On Monomer Actin Atpase Activitymentioning
confidence: 85%
“…The enhancement of spontaneous actin nucleation and the generation of short polymers (oligomerization) by low concentrations of MgC12 has been repeatedly observed (Maruyama, 1981;Tobacman & Kom, 1983;Mozo-Villarias & Ware, 1985;Newman et al, 1985). This observation can be accounted for by the formation of Mg-actin in the actin population, and the facilitated formation of nuclei or oligomers by Mg-actin is attributed to a lower free energy of nucleation for Mg-actin than for Ca-actin (Oosawa & Asakura, 1975;Oosawa, 1983;Tobacman & Kom, 1983;Newman et al, 1985).…”
Section: Nucleationmentioning
confidence: 86%
See 1 more Smart Citation
“…Mg-actin assumes a F-monomer-like conformation so that it has higher ATPase activity than Ca-actin. However, there are oligomers in Mg-G-actin solutions even at subcritical concentrations, although no filaments are detectable (27,28). Thus, the higher ATPase activity of Mg-G-actin may result from transient oligomer formation from Mg-G-actin rather than from a more active monomer.…”
Section: Discussionmentioning
confidence: 97%
“…Although the x-ray patterns show that the G-actin solution contained a homogeneous population of monomers, we would not have been able to detect small qligomqrs in our solutions if they had constituted less than 5% of the-species. Since quasielastic light scattering (39,40,45) has demonstrated that gel-filtered actin always contains trace amounts of oligomers, these nuclei could rapidly (within 50 msec) convert a near homogeneous solution of actin monomers into a large population of short oligomers. However, two pieces of evidence suggest that this explanation is not correct.…”
Section: Methodsmentioning
confidence: 99%